Manikam Kalbu and Nusantara Women: An Inquiry into Regional Female Expertise and Knowledge (KEMANUSIAAN The Asian Journal of Humanities, 2023)
What was the role of women as gatekeepers and users of technology before its modernisation and institutionalisation in Nusantara? How were they custodians of specific knowledge formed in and around the Malay world? There is no adequate amount of information in the archives for these questions to be answered sufficiently, but in Manikam Kalbu, Faisal Tehrani’s novel about two Malay seamsters set in a parallel period—the Malaccan sultanate in the 16th century and Malaysia in the 20th century—elicits the profound mastery of the material, tools, and art of sewing and craftsmanship by female characters who were depicted as caretakers of traditional knowledge and gatekeepers of their respective craft. Such depictions are either skewed or non-existent in Malay or Indonesian historiography, as many historical narratives are male-centric or focused on the political participation or domestic roles of women as wives and mothers. This study aims to uncover traces of historical reality from Faisal Tehrani’s fictional world as a means to fill the gap in historical literature and paint a critical and often absent picture of women in Nusantara, their expertise, their knowledge and the continuities of traditional and indigenous knowledge.